Sailing Through History: The Legacy of Medieval Sea Trade On Migrant Perception and Extreme Right Voting - Anna Bottasso; Gianluca Cerruti; Maurizio Conti; Marta Santagata (Institute of Labor Economics (IZA), 2024)
In this study we evaluate the role that Mediterranean Medieval trade with Africa and the Middle-East still plays today in Italian politics by shaping the attitudes towards migrants of individuals that live close to Medieval ports. Trade connections between Medieval ports and Muslim Africa and Middle East might have indeed favoured the emergence of cultural traits that helped the interaction with foreigners from different cultures, ethnicity and religion a few centuries before with respect to other areas of the country. We use a representative survey of young individuals (aged 20-35) to show that, conditionally on a rich set of geographic, historic, economic and individual controls, people living close to a Medieval port are less likely to think that migrants make Italy an unsafe place as well as to report right-wing voting attitudes. Moreover, we also find, in those areas, a lower probability of xenophobic attacks during the spike of refugees from Siria of 2015. Interestingly, right-wing parties started to attract less votes near Medieval ports only when immigration had become a very salient issue. Similarly, we find a lower probability of Jewish deportations close to Medieval ports during the Nazi occupation, the only period in Italian contemporary history when a minority group was explicitly targeted by the government. This in turn suggests that some deep-rooted cultural traits, although not observed and not clearly at work in society, can become visible when the right historical and political circumstances take place.
Keywords: D72; N70; N90; O10; O12; P48; 330; political ideology; immigration; cultural transmission; medieval trade sea routes; Roman road network